Integration of Governance, Risk, and Compliance as Parameters for Determining Business Judgment Rules in Legal Protection Efforts for Directors - Tina Amelia; Mohamad Ismed (Law Development Journal, 2026)
The purpose of this research is to examine the GRC integration as a normative and empirical parameter for the utilization of the doctrine of the Business Judgment Rule (BJR). The integration of GRC acts as a legal safeguard for the Board of Directors in state-owned enterprises (SOEs). This research will utilize the socio-legal approach and empirical qualitative method. Data collection will be done by conducting in-depth interviews and documentation at "Company X" which is the largest SOE in Indonesia. The findings from this study show that the GRC integration at Company X has evolved into a legal parameter which changes the abstract Business Judgment Rule (BJR) doctrine into concrete audit trail evidence. Specifically, the Governance pillar acts as a manifestation of good faith with regards to transparency. The Risk Management pillar manifests the rule of prudence through thorough risk analysis (well-informed). Compliance provides legality for the actions within their jurisdiction (intra vires). This combination of these three has proven to be effective in ensuring that there is enough legal defense put into place for directors of SOEs, thus creating enough legal certainty in the process of making decisions and minimizing criminalization risks from loss making in business.